Social discrimination in community forestry: Socio-economic and gender perspectives - Parajuli, R; Pokharel, RK; Lamichhane, D (Banko Janakari, 2011)
A study was carried out to analyze the existing social discrimination among Community Forest User Group (CFUG) members. Two CFUGs representing heterogeneous ethnic groups in Syangja district were selected to examine the participation of CFUG members in Community Forestry (CF) activities, benefit sharing and fund mobilization system. PRA/RRA tools like questionnaire survey, wealth ranking, key informant survey, triangulation, and informal discussion were employed to generate primary data. Statistical parameters such as percentage, mean, ANOVA, and contingency coefficient were used to interpret this data. The perception of local people was measured on the five point Likert scale, and Chi-square test was applied to interpret this result. The participation of the poor, disadvantaged group and women were minimal in CF activities but their presence was more at the time of forest product distribution. Timber had been distributed less to the poor and disadvantaged group (DAG) households than to others. More than 65% CFUG members were unaware about CFUG fund. Their overall perceptions of CF management were not positive. The result clearly demonstrated discrimination between the rich and the poor, male and female, and DAG and non-DAG within the CFUG. Key words: Community forest user group; discrimination; participation; disadvantaged group; poor DOI: 10.3126/banko.v20i2.4799 Banko Janakari Vol.20(2) 2010 pp.26-33